A techno-sustainable bio-waste management strategy for closing chickpea yield gap. (1st January 2021) - Ozdemir, Saim; Ozdemir, Serkan; Ozer, Hasan; Yetilmezsoy, Kaan
Graphical abstract: Highlights: Poultry abattoir sludge stimulates nodulation, nitrogen fixation, and chickpea yield. PAS application rate of 50 kg N ha −1 markedly enriches biomass and grain yields. PAS amendment boosts chickpea yield up to 45% in low fertility and high pH soil. Image analysis plays a pivotal role to clarify effects of PAS on chickpea yield. PAS application to marginal lands suggests a sustainable way for chickpea production. Abstract: Sustainable development goals imply environmentally sound management of all wastes to minimize the waste generation through prevention, reduction, recycling, and reuse. In particular, the poultry industry produces nutrient-rich waste that requires proper management. Additionally, the recycling of bio-wastes in agricultural lands is still a key technology for the sustainable use of nutrients as a renewable fertilizer. Currently, there are very few studies on the utilization of agro-industrial bio-wastes, such as poultry abattoir sludge (PAS), for crop cultivation in soils containing low organic matter and high pH. In this context, it is necessary to make a more particular assessment of poultry industry-oriented and locally available nutrient-rich organic wastes for nodulation, physiological adaptation, and crop yield. Considering the scarcity of the literature in this field, the present study aimed to fulfill the apparent gap by focusing on the applicability of recycled PAS to low fertility soil in the growth of chickpea selected as a model legume, thereby contributing to the development of an agricultural and sustainable industrial management strategy for the relevant sectors. In this study, leaf chlorophyll content and nodule color were also investigated by the image analysis methodology to describe the effects of bio-waste on closing chickpea yield gap in a marginal land with high soil pH and low organic matter. Two-year consecutive field experiments were carried out to explore the effect of the PAS with the application rates of 25 kg N ha −1 (T2 ), 50 kg N ha −1 (T3 ), and 100 kg N ha −1 (T4 ) along with unamended (T0 ) and fertilized control (T1 ). The results indicated that the PAS treatments significantly differed in chlorophyll content, nodulation parameters, and biomass and grain yields. The chlorophyll content was correlated ( r = 0.910) with the red color value (RGB color model) of nodule image analysis in the response to bio-waste. Based on the two-year average, it was concluded that chickpea yield could be increased 45% by amending with the PAS (T3 ). The present study clearly demonstrated that the image analysis could be a useful digital tool for the evaluation of chlorophyll content, nitrogen fixation efficiency, and forecasting biomass and grain yields of chickpea. The results also confirmed that the PAS application to low fertility soil could prominently contribute to establish sustainable waste management and crop production alternatives for closing chickpea yield gap.